Analisis Penerapan Model Pembelajaran Kreatif dan Inovatif Berbasis Hots di Era Digital - Zahra Nur Fadila; Suyit Ratno; Zahra Fadila Nst; Fauziah Nur Panjaitan; Naomi Priska Aprilia Hutapea; Meita Krisnadya Lumban Gaol; David Sitepu; Hanny Pebri Olivia (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The implementation of creative and innovative learning models based on Higher Order Thinking Skills (HOTS) in the digital era is a must in an effort to improve the quality of education that is relevant to the challenges of the times. This study aims to analyze the effectiveness of the implementation of creative and innovative learning models based on HOTS in the digital era and identify supporting and inhibiting factors in the process. This study uses a qualitative descriptive research method. Data collection was carried out using interview and observation guidelines. Data analysis was carried out in stages, data reduction, data presentation and drawing conclusions. The results of the study indicate that the creative and innovative learning mode approach based on HOTS is very important to improve students' critical and creative thinking skills, which are the main needs in facing the challenges of the 21st century.